Supply Chain Strategy of Charge for Technological Connection to Electricity Networks in Electric Industry - Ya. Afanassyev, Valentin; G.Lyubimova, Natalia; F.Ukolov, Vladimir; S.Flaksman, Alina (ExcelingTech, 2019)
Improving the quality of service and the availability of electrical networks for consumers stimulates an increase in the pace of economic development and implies reduction in the cost of technological connection of power-consuming devices to electrical networks by supply chain management. In Russia, approaches to the cost accounting for technological connection to electrical networks and calculation of charge for technological connection, which made a significant amount for consumers until recently, are constantly changing. Despite the varied practice of organizing and paying for technological connection to the electrical network abroad, there is no unified approach to cost accounting and arrangement of work on technological connection to electrical network in the world. In Russia, at present, a methodology has been adopted for unification of standardized tariff rates for work on technological connection for all territorial grid organizations of constituent entities of the Russian Federation. A significant amount of the costs of technological connection to the electrical networks of energy consuming installations of the population, medium and small businesses has been transferred to a single-rate or to the rate for maintaining a two-rate (three-rate) tariff for electricity transmission services. As a result, the charge for technological connection of certain categories of consumers has significantly decreased and Russia's world rating has increased in terms of the indicator â€œConnection to electrical supply networksâ€, but the tariffs for electricity transmission services for existing â€œoldâ€ consumers have increased. In the context of artificial restraining of tariffs for electricity transmission by the Russian state, the losses of grid organizations have increased and the question remains about the ownership of property built at the expense of consumers for technological connection to consumers' power grids. The authors analyze the indicators of PJSC ROSSETI for technological connection to electrical networks, and justify a tendency on reduction in the costs of power supply network organizations for technological connection to electric grids with an increase in the number of contracts concluded with consumers. They also propose to cancel the charge for technological connection of power-consuming devices of certain categories of consumers, and also to introduce compensation for costs of the remaining categories of consumers.